Adjuvant Chemotherapy and Trastuzumab Is Safe and Effective in Older Women With Small, Node-Negative, HER2-Positive Early-Stage Breast Cancer - Cadoo, Karen A. (Clin Breast Cancer, 2016)
The benefit of adjuvant trastuzumab with chemotherapy in breast cancer is well-established; however, its impact on outcomes for older women with small, node-negative, human epidermal growth factor receptor 2-positive disease is less clear and unlikely to be addressed in prospective studies. This retrospective, sequential cohort study suggests adjuvant trastuzumab with chemotherapy results in excellent breast cancer outcomes with few cardiac events in this population. INTRODUCTION: The benefit of adjuvant trastuzumab with chemotherapy is well established for women with higher risk human epidermal growth factor receptor 2-positive (HER2(+)) breast cancer. However, its role in older patients with smaller, node-negative tumors is less clear. We conducted a retrospective, sequential cohort study of this population to describe the impact of trastuzumab on breast cancer outcomes and cardiac safety. PATIENTS AND METHODS: Women ≤ 55 years with ≥ 2 cm, node-negative, HER2(+) breast cancer were identified and electronic medical records reviewed. A no-trastuzumab cohort of 116 women diagnosed between January 1, 1999 and May 14, 2004 and a trastuzumab cohort of 128 women diagnosed between May 16, 2006 and December 31, 2010 were identified. Overall survival and distant relapse-free survival were estimated by Kaplan-Meier methods. RESULTS: The median ages of the trastuzumab and no-trastuzumab cohorts were 62 and 64 years, respectively. More patients in the trastuzumab cohort had grade III (P = .001), lymphovascular invasion (P = .001), or estrogen receptor-negative (P < .001) cancers. The majority of the trastuzumab cohort received chemotherapy versus one-half of the no-trastuzumab cohort (98% vs. 53%; P < .0001). The median follow-up was 4 versus 9 years in the trastuzumab versus no-trastuzumab cohorts; therefore, outcomes at 4 years are reported. Despite the higher-risk tumor features in the trastuzumab group, the 4-year overall survival was 99% in both cohorts; the distant relapse-free survival was 99% versus 97% in the trastuzumab versus no-trastuzumab cohorts. Four (3.1 %; 95% confidence interval, 1.0%–7.8%) women in the trastuzumab cohort and 1 in the no-trastuzumab cohort developed symptomatic heart failure. There were no cardiac-related deaths in either arm. CONCLUSION: Following adjuvant trastuzumab with chemotherapy, selected older women with small, node-negative, HER2(+) breast cancers have excellent disease control. The rate of cardiac events is low.